2022
DOI: 10.29165/ajarcde.v4i3.88
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Fatty Acid and Sensory Profile of Cocoa Butter Produced from Fermented and Non-Fermented Cocoa Butter

Abstract: The study aimed to explore the influence of fermentation and non-fermentation on cocoa processing (Theobroma cacao L.) on physical properties, chemical properties, fatty acid profiles and sensory properties of cococa butter. The study was conducted using an experimental method with two treatments and three replications. Analysis of cocoa butter consisted of yield, color, moisture content, free fatty acids,  iod numbers, peroxide numbers, determination of fatty acid profile using GC-MS, and analysis of sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…On the other hand, the darker coloration observed in the four treatments compared to the commercial sample may be linked to factors related to the soil conditions of copoazú growth. However, it is more likely associated with the fermentation process, as noted in a study on Theobroma cacao, where it was shown that fermentation significantly influences butter coloration [20,21]. This difference is also influenced by the unknown fermentation process of the commercial sample.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, the darker coloration observed in the four treatments compared to the commercial sample may be linked to factors related to the soil conditions of copoazú growth. However, it is more likely associated with the fermentation process, as noted in a study on Theobroma cacao, where it was shown that fermentation significantly influences butter coloration [20,21]. This difference is also influenced by the unknown fermentation process of the commercial sample.…”
Section: Discussionmentioning
confidence: 97%
“…As extensively researched, the fermentation of Theobroma grains leads to changes in both physical and chemical properties. Various enzymatic reactions alter components such as polyphenols, proteins, and carbohydrates, among others [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…Menambahkan S. cerevisiae, L. lactis, dan A. aceti ke fermentasi biji kakao segar dapat meningkatkan suhu fermentasi, sehingga mempercepat proses fermentasi Kusuma et al, 2020). Oleh karena itu, diharapkan penambahan ragi NKL akan mempercepat konversi gula menjadi asam asetat, sehingga mempercepat suhu kematian benih (Andriani et al, 2020).…”
Section: Perubahan Warna Keping Biji Selama Fermentasi (Cut Test)unclassified